2008
DOI: 10.1007/s00292-007-0957-z
|View full text |Cite
|
Sign up to set email alerts
|

Primäre neuroendokrine Karzinome der Leber

Abstract: Primary hepatic neuroendocrine tumors are rare neoplasms. While primary hepatic carcinoid tumors (PHCT) are well-differentiated tumors, primary hepatic small-cell carcinomas (PHSCC) represent the poorly differentiated end of the spectrum of neuroendocrine carcinomas. The first patient, suffering from PHCT, has had a follow-up for 32 years and is still alive. Within this time, the tumor relapsed 4 times with unchanged histology and immunohistochemistry features. The second patient suffered from small-cell carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…[ 2 ] Primary hepatic neuroendocrine neoplasms (PHNENs) are extremely rare, with less than 200 cases reported throughout the English-language literature since Edmondson first described this disease in 1958. [ 3 17 ] It has been suggested that PHNEN cells originate from ectopic pancreatic and/or adrenal tissue in the liver or from scattered neuroendocrine cells in the intrahepatic biliary epithelium. [ 15 , 18 ] Another hypothesis is that the neuroendocrine differentiation of a single malignant stem cell provides the major contribution to the genesis and morphology of PHNENs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Primary hepatic neuroendocrine neoplasms (PHNENs) are extremely rare, with less than 200 cases reported throughout the English-language literature since Edmondson first described this disease in 1958. [ 3 17 ] It has been suggested that PHNEN cells originate from ectopic pancreatic and/or adrenal tissue in the liver or from scattered neuroendocrine cells in the intrahepatic biliary epithelium. [ 15 , 18 ] Another hypothesis is that the neuroendocrine differentiation of a single malignant stem cell provides the major contribution to the genesis and morphology of PHNENs.…”
Section: Introductionmentioning
confidence: 99%
“…Endokrine Karzinome der Leber [28], das primäre lokalisierte epithelioide Mesotheliom [29] und der adrenale Resttumor erweitern das differenzialdiagnostische Spektrum um Entitäten, die in der aktuellen WHO-Klassifikation der Lebertumoren nicht gelistet sind. Auch normales Nebennierengewebe kann in kleinen Biopsien einen hepatozellulären Tumor vortäuschen.…”
Section: Sehr Seltene Primärtumorenunclassified